Traumatic brain injury induces an adaptive immune response in the meningeal transcriptome that is amplified by aging - Buenaventura, Ruchelle G.; Harvey, Alex C.; Burns, Mark P.; Main, Bevan S. (Frontiers in Neuroscience, 2023)
Traumatic Brain Injury (TBI) is a major cause of disability and mortality, particularly among the elderly, yet our mechanistic understanding of how age renders the post-traumatic brain vulnerable to poor clinical outcomes and susceptible to neurological disease remains poorly understood. It is well established that dysregulated and sustained immune responses contribute to negative outcomes after TBI, however our understanding of the interactions between central and peripheral immune reservoirs is still unclear. The meninges serve as the interface between the brain and the immune system, facilitating important bi-directional roles in healthy and disease settings. It has been previously shown that disruption of this system exacerbates inflammation in age related neurodegenerative disorders such as Alzheimer's disease, however we have an incomplete understanding of how the meningeal compartment influences immune responses after TBI. Here, we examine the meningeal tissue and its response to brain injury in young (3-months) and aged (18-months) mice. Utilizing a bioinformatic approach, high-throughput RNA sequencing demonstrates alterations in the meningeal transcriptome at sub-acute (7-days) and chronic (1-month) timepoints after injury. We find that age alone chronically exacerbates immunoglobulin production and B cell responses. After TBI, adaptive immune response genes are up-regulated in a temporal manner, with genes involved in T cell responses elevated subacutely, followed increases in B cell related genes at chronic time points after injury. Pro-inflammatory cytokines are also implicated as contributing to the immune response in the meninges, with ingenuity pathway analysis identifying interferons as master regulators in aged mice compared to young mice following TBI. Collectively these data demonstrate the temporal series of meningeal specific signatures, providing insights into how age leads to worse neuroinflammatory outcomes in TBI.